Giải hệ phương trình sau: a, 2x- y= 5 b,x+ 2y= 3 c, 2x+ 3y= 5 x+ y= -2 x- 4y= 3

Giải hệ phương trình sau:
a, 2x- y= 5 b,x+ 2y= 3 c, 2x+ 3y= 5
x+ y= -2 x- 4y= 3 3x+ 2y= 5

0 bình luận về “Giải hệ phương trình sau: a, 2x- y= 5 b,x+ 2y= 3 c, 2x+ 3y= 5 x+ y= -2 x- 4y= 3”

  1. Đáp án:

     

    Giải thích các bước giải:

     a,$\left \{ {{2x- y= 5} \atop { x+ y= -2 }} \right.$ 

    ⇒$\left \{ {{2x- y= 5} \atop {2x+2y=-4 }} \right.$ 

    ⇒$\left \{ {{2x- y= 5} \atop {-3y=3}} \right.$ 

    ⇒$\left \{ {{y=-1} \atop {2x- (-1)= 5}} \right.$

    ⇒ $\left \{ {{y==1} \atop {2x=4}} \right.$ 

    ⇒$\left \{ {{y=-1} \atop {x=2}} \right.$

    vậy x=2;y=-1

    b,$\left \{ {{x+ 2y= 3 } \atop {x- 4y= 3}} \right.$ 

    ⇒$\left \{ {{6y=0} \atop {x- 4.0= 3}} \right.$ 

    ⇒$\left \{ {{y=0} \atop {x=3}} \right.$ 

    vậy x=3;y=0

    c,$\left \{ {{2x+ 3y= 5} \atop {3x+ 2y= 5}} \right.$ 

    ⇒$\left \{ {{6x+ 9y= 15} \atop {6x+ 4y=10}} \right.$ 

    ⇒$\left \{ {{5y=5} \atop {3x+ 2y= 5}} \right.$ 

    ⇒$\left \{ {{y=1} \atop {3x+ 2.1= 5}} \right.$ 

    ⇒$\left \{ {{y=1} \atop {x=1}} \right.$

    vậy x=1;y=1

    Bình luận

Viết một bình luận